Public Debt and Economic Growth: Evidence From Africa - Lartey, Emmanuel Yeboah; Musah, Alhassan; Okyere, Bismark; Yusif, Abdul-Nasir (International Journal of Economics and Financial Issues, 2018)
There is no doubt that every country needs funding to foster economic growth and development. However, such funding needs to be at levels deemed sustainable and closely in line with the government’s fiscal and monetary policies. To this end, there is an urgent need for policymakers in governments, central banks, and international policy organizations to understand the effects of public debt on economic growth. This study used 50 African countries from 1980 to 2015 to assess the impact of public debt on economic growth. The study employed an Ordinary Least Square (OLS) estimation technique for a static panel regression model and the Generalised Method of Moment (GMM) estimation technique for a dynamic panel regression model for the analysis. The empirical results from both estimation techniques suggest a statistically significant negative relationship between public debt and economic growth. The results also provide evidence that the relationship between public debt and economic growth is non-linear. The study also found that inflation and government consumption expenditure have a statistically significant negative relationship with economic growth whereas capital formulation, population growth and openness of trade have a statistically significant positive relationship with economic growth. Keywords: Public Debt, Economic Growth, OLS, GMM JEL Classifications: F33, F34, F35, O11 DOI: https://doi.org/10.32479/ijefi.7057